Composite enhanced high-temperature durable converter slag-stopping sliding plate brick and preparation method thereof

By introducing materials such as ZrB2, Al3BC3 and B4C into the converter slag stop skateboard bricks to form a composite protective film, the problems of peeling and wear of traditional skateboards in high-temperature environments are solved, high-temperature durability and economy are achieved, and it is suitable for large-scale use.

CN119841628APending Publication Date: 2025-04-18MAANSHAN LIER KAIYUAN NEW MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411760123.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Traditional inlaid zirconium skateboards and aluminum-zirconium carbon skateboards have problems such as peeling and wear in high temperature environments, resulting in failure during long-term use and high production costs, making it difficult to meet the needs of large-scale and long-term use.

Method used

By introducing high-efficiency composite antioxidants such as zirconium diboride (ZrB2), Al3BC3 ceramic powder and boron carbide (B4C), a composite enhanced high-temperature durable converter slag barrier skate brick is designed to form a multi-layer composite protective film to improve oxidation resistance, wear resistance and thermal shock stability.

Benefits of technology

It significantly improves the high-temperature oxidation resistance, wear resistance and thermal shock stability of the skateboard, extends its service life, reduces production costs, and is suitable for large-scale promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses a composite enhanced high-temperature durable converter slag-stopping sliding plate brick and a preparation method thereof, and belongs to the technical field of converter slag-stopping sliding plate bricks. The problem that an existing material is insufficient in durability in the high-temperature steel slag scouring and oxidizing environment is solved. By introducing efficient composite antioxidants such as zirconium diboride (ZrB2), Al3BC3 ceramic powder and boron carbide (B4C), a multi-layer composite protective film is designed, and the oxidation resistance, wear resistance and thermal shock resistance of the sliding plate are improved. In the preparation process of the material, a high-temperature hot-pressing sintering process is adopted, and the microstructure and performance of the material are systematically characterized. Test results show that the composite sliding plate material still has excellent oxidation resistance and scouring resistance at the high temperature of 1600 DEG C, the thermal shock resistance is remarkably improved, and the breaking strength and the compression strength are improved by about 20% and 30% respectively compared with those of a traditional sliding plate material. The service life of the slag stopping sliding plate is effectively prolonged, and meanwhile the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of converter slag retaining slide bricks, and in particular to a composite enhanced high-temperature durable converter slag retaining slide brick and a preparation method thereof. Background Art

[0002] Converter steelmaking is one of the core technologies of efficient and high-temperature metallurgy. It is a key refractory component in high-temperature steelmaking production. Its main function is to control the flow of steel slag, separate impurities in molten steel, and ensure the smooth progress of the steelmaking process. The slag-blocking slide material not only needs to maintain structural stability at high temperatures, but also needs to have high wear resistance, corrosion resistance and oxidation resistance to cope with the erosion of high-temperature molten steel and oxidizing atmosphere. However, traditional slide materials such as inlaid zirconium slides and aluminum zirconium-carbon slides will have different degrees of peeling, wear and other problems during long-term use, resulting in slide failure. Although the inlaid zirconium slide can provide higher oxidation resistance, its manufacturing cost is high and its thermal shock resistance is insufficient; while the aluminum zirconium-carbon slide has poor oxidation resistance and wear resistance, which is difficult to meet the needs of long-term use of the converter. Therefore, the development of a composite reinforced slag-blocking slide material with high-temperature durability has become a key technical problem.

[0003] At present, slag-blocking slides are mainly divided into two types of materials: inlaid zirconium slides and aluminum-zirconium-carbon slides. Among them, inlaid zirconium slides mainly rely on high-purity zirconium oxide (ZrO2) to achieve high-temperature and oxidation resistance, and are widely used in high-temperature metallurgical environments; while aluminum-zirconium-carbon slides improve the slide's corrosion and impact resistance through a combination of aluminum, zirconium and carbon. These two types of slide materials meet the slag-blocking requirements to a certain extent, but there are still many challenges in terms of durability and production costs.

[0004] Deficiencies of existing technologies:

[0005] (1) Disadvantages of inlaid zirconium slides

[0006] High production cost: The main component of zirconium inlaid skateboards is zirconium oxide, which has high material cost and strict processing requirements, resulting in high overall production costs and is not suitable for large-scale, long-term use.

[0007] Instability of the inlay process: Zirconia and the skateboard substrate are combined through the inlay process, but due to the large difference in thermal expansion coefficients between the two, thermal stress is easily generated during the high-temperature cooling cycle, causing the skateboard to crack and the zirconium oxide layer to fall off or peel off, directly affecting the service life of the skateboard.

[0008] Influence of structural defects: The inlay process will leave a fireclay gap between the zirconium plate and the body, usually 2-4mm. This will cause steel slag and oxidizing gases to penetrate into the fireclay gap, further aggravating the oxidation damage of the skateboard and weakening the structural stability of the skateboard.

[0009] (2) Disadvantages of aluminum zirconium carbon slide plates

[0010] Insufficient oxidation resistance: The main components of aluminum zirconium carbon skateboards, carbon and aluminum, are easily oxidized in a high-temperature oxidizing atmosphere, causing the skateboard's surface protective layer to be quickly consumed and peeled off, thereby accelerating the skateboard's failure.

[0011] Poor erosion resistance and wear resistance: Under the erosion of high-temperature molten steel and steel slag, the surface of the aluminum-zirconium-carbon skateboard is easily worn and eroded, especially in the anti-slip area. The oxide layer of the skateboard is thin and cannot provide long-term and efficient protection, which in turn affects the slag blocking effect.

[0012] Poor thermal shock stability: Due to the easy loss of carbon components, aluminum zirconium carbon slides are prone to cracks during repeated high-temperature heating and cooling, resulting in material spalling and slide failure. Summary of the invention

[0013] The purpose of the present invention is to provide a composite enhanced high-temperature durable converter slag-blocking slide brick and a preparation method thereof. In terms of material design, zirconium diboride (ZrB2), Al3BC3 ceramic powder, boron carbide (B4C) and other high-efficiency composite antioxidants are introduced to improve the high-temperature oxidation resistance, wear resistance and thermal shock stability of the slide material. The present invention has the following innovative features:

[0014] Innovative composite antioxidant system: By introducing ceramic powders such as ZrB2 and Al3BC3, the skateboard can form a multi-layer composite protective film in a high-temperature oxidation environment, especially the multi-layer structure of ZrO2, Al2O3, B2O3, etc., which can not only effectively prevent oxygen penetration, but also have good thermal shock self-healing ability, greatly improving the skateboard's antioxidant and anti-stripping properties.

[0015] Enhanced erosion and wear resistance: The addition of zirconium diboride and boron carbide makes the slide plate show higher wear resistance and erosion resistance under the erosion of high-temperature molten steel and steel slag. These components form a stable oxide layer in the high-temperature environment of molten steel, effectively resisting the erosion and erosion of steel slag and extending the service life of the slide plate.

[0016] Excellent thermal shock stability: The composite oxide layer structure gives the skateboard a good thermal expansion coefficient matching ability, which can effectively resist the influence of thermal stress in a high temperature fluctuation environment, thereby avoiding problems such as cracks and peeling caused by thermal shock, and ensuring the stability and efficiency of the skateboard.

[0017] Economical and manufacturable: The present invention uses zirconium diboride and Al3BC3 as core reinforcement materials, optimizes material costs, and replaces the high-content zirconium oxide in the expensive zirconium-inlaid slide. While maintaining high performance, it significantly reduces production costs and has economic feasibility for large-scale promotion.

[0018] In summary, the present invention, based on the traditional slag-blocking slide technology, realizes high-temperature oxidation resistance, wear resistance, spalling resistance and good thermal shock stability through composite reinforced material design. Compared with the existing inlaid zirconium slides and aluminum zirconium carbon slides, the composite reinforced high-temperature durable converter slag-blocking slide material of the present invention can more effectively meet the complex needs in the high-temperature steelmaking environment, significantly reduce the production cost while ensuring long-term use, and has significant innovation and practicality. The problems raised in the above-mentioned background technology are solved.

[0019] To achieve the above object, the present invention provides the following technical solution: a composite reinforced high-temperature durable converter slag-blocking slide brick, comprising granular material, premixed powder and a binder, wherein the components and mass fractions of the granular material are as follows:

[0020]

[0021] The components and mass fractions of the premixed powder are as follows:

[0022]

[0023]

[0024] The components and mass fractions of the binder are as follows:

[0025] 2-4 parts of thermosetting phenolic resin;

[0026] 2 to 4 parts of silicone resin.

[0027] Preferably, w(Al2O3) in the fused zirconium corundum is ≥72.5%, w(SiC) in silicon carbide is >98wt%; w(Al2O3) in granular plate-like corundum and plate-like corundum powder is ≥99%, and the volume density of granular plate-like corundum is 3.5g·cm-3; w(C solid content) in thermosetting phenolic resin is ≥50%.

[0028] Preferably, in the metal aluminum powder, w(Al)≥99.5% and the mesh size is 500 meshes.

[0029] Preferably, the particle size of the a-Al2O3 micropowder is 0 to 3 μm; the chemical composition and main content of the a-Al2O3 micropowder are: Al2O3 content ≥ 99.0wt%, SiO2 content ≤ 0.1wt%, Fe2O3 content ≤ 0.08wt%, Na2O+K2O content ≤ 0.3wt%.

[0030] Preferably, in the silicon carbide powder, w(SiC)≥99% and the particle size is 3 μm.

[0031] Preferably, the boron carbide powder has a Mohs hardness of 9.3, a relative density (d204) of 2.508-2.512, and a melting point of 2350°C.

[0032] The present invention provides another technical solution: a method for preparing a composite enhanced high-temperature durable converter slag retaining slide brick, comprising the following steps:

[0033] S1. First, mix the granular materials evenly according to the proportion;

[0034] S2, then dry-mixing the composite powders in proportion under vacuum conditions to form a premixed powder;

[0035] S3, then the granular material, premixed powder, thermosetting phenolic resin and silicone resin are mixed at high speed;

[0036] S4. Finally, the finished product is obtained after pressing, drying and fine processing.

[0037] Preferably, the steps of preparing the composite enhanced high temperature durable converter slag retaining slide brick by using the raw material components and proportions of the granular material, premixed powder and binder are as follows:

[0038] S1. Ingredients of granular materials: granular materials are prepared according to the mass proportion of raw materials; 15 parts of 3-1 mm fused zirconium corundum, 25 parts of 2-1 mm plate corundum, 15 parts of 1-0 mm plate corundum, and 5 parts of 1-0 mm silicon carbide;

[0039] S2, premixed powder: 20 parts of 325 mesh plate-shaped corundum fine powder, 3 parts of 325 mesh Al3BC3 micropowder, 3 parts of 3μm mesh ZrB2 micropowder, 8 parts of a-Al2O3 micropowder, 2 parts of 1000 mesh SiC powder, 5 parts of 500 mesh metal Al powder, 1 part of 325 mesh boron carbide, and 1 part of carbon black were dry-mixed in a vacuum high-speed mixer for 30 minutes to evenly disperse the fine powder components. After dispersion, the fine powder components were packed and sealed for later use;

[0040] S3, high-speed mixing: the granular material prepared in step 1 is mixed with the premixed powder in step 2, and thermosetting phenolic resin and high-temperature silicone resin are added and mixed for 10 to 15 minutes. The mixed mud is kept in a constant temperature room for 8 to 10 hours. The constant temperature room is required to maintain a temperature of 25 ± 3 ° C and a relative humidity of 45 to 65%;

[0041] S4, molding: the clay trapped in the constant temperature and humidity chamber in step 3 is molded into a semi-finished blank using a LAEIS 2500-ton hydraulic press;

[0042] S5, drying: the semi-finished blank prepared in step 4 is naturally cooled for 12 to 16 hours, and then enters the electric kiln dryer. The drying temperature is divided into two stages. The first stage is heated at a uniform rate of 20°C per hour to 110°C and then kept warm for 24 hours. The second stage is heated at a uniform rate of 15°C per hour to 300°C and kept warm for 24 hours.

[0043] S6, making steel hoops: after the fired product in step 5 is cooled to room temperature, a Q235 cold-rolled steel hoop with a thickness of 5 mm and a width of 35 mm is hot-fitted on the converter slide body to prevent the expansion and extension of cracks when the product is used;

[0044] S7, grinding: the converter slide brick with steel hoop in step 6 is finely ground by CNC grinder, and after the flatness reaches 0.03mm, it is infrared dried at 200℃ for 0.5h and then prepared for the next process;

[0045] S8, coating: coating the skateboard bricks finely ground in step 7 with a special high temperature resistant coating, and obtaining the finished product after natural drying.

[0046] Preferably, in step 2, a planetary vibrating high-energy ball mill is used for vacuuming; and in step 3, an EIRICH high-power mixer is used for uniform mixing.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] 1. The present invention proposes a composite reinforced high-temperature durable converter slag-blocking slide brick and a preparation method thereof. The aggregate is made of fused zirconium corundum and plate-shaped corundum as the matrix, and various high-efficiency antioxidant enhancers such as ZrB2 micropowder, Al3BC3 micropowder, metal aluminum powder, silicon carbide, and boron carbide are added. This design can form a multi-layer composite protective film. The composite oxide layer structure gives the slide a good thermal expansion coefficient matching ability, and can effectively resist the influence of thermal stress in a high-temperature fluctuation environment, thereby avoiding cracks and peeling caused by thermal shock, and ensuring the stability and efficiency of the slide.

[0049] 2. The present invention proposes a composite reinforced high-temperature durable converter slag-blocking slide brick and a preparation method thereof. ZrB2 is preferentially oxidized at high temperature to form a dense ZrO2 layer, which prevents further penetration of the oxidizing atmosphere. Al2O3 and B2O3 generated by oxidation of Al3BC3 fill the microcracks in the ZrO2 layer to form a multi-layer composite protective film, providing long-term anti-oxidation protection. At the same time, the multi-layer composite structure formed by materials such as ZrB2 and Al3BC3 can effectively disperse thermal stress and avoid crack propagation in high temperature environments.

[0050] 3. The present invention proposes a composite enhanced high-temperature durable converter slag-blocking slide brick and a preparation method thereof. Aluminum boron carbon (Al3BC3) is a new type of material, and its crystal structure belongs to the hexagonal P63 / mmc point group structure. The bonding between particles in the crystal is in the form of triangular bipyramids arranged in an alternating pattern. This special crystal structure gives Al3BC3 material high hardness, excellent thermal and chemical stability, and good oxidation resistance at medium temperatures. By adding Al3BC3 as a sintering aid to composite SiC in the matrix, Al3BC3 material can not only promote the sintering of ceramic materials, but also significantly improve the fracture toughness of the material.

[0051] 4. The present invention proposes a composite reinforced high-temperature durable converter slag-blocking slide brick and a preparation method thereof. The B4C and SiC matrix play a role similar to a "skeleton", that is, the physical properties have extremely high hardness in the steel slag scouring environment. By adding boron carbide and silicon carbide, the slide shows higher wear resistance under the slag scouring, effectively resisting the erosion of the material surface and preventing the wear of the material surface. In terms of chemical reaction, B4C generates B2O3, SiC generates SiO2, SiO2 and Al2O3 can generate Al2SiO5 composite oxide layer at high temperature, and these oxidation products not only form an anti-oxidation barrier, but also further form a dense composite oxide layer with other oxides. The composite glass phase formed by B2O3, SiO2 and Al2O3 further enhances the integrity of the oxide film, prevents the oxide layer from peeling off, and has a self-healing function, thereby showing better anti-oxidation performance under severe temperature fluctuations. 7Zr02+5B4C=7ZrB2+3B203+5CO From the B4C in the material in the reaction formula, the oxidation product ZrO in the material can be reduced to ZrB2, thereby reducing the oxidation degree of the raw material and further improving the oxidation resistance of the ZrB2 material.

[0052] 5. The composite reinforced high-temperature durable converter slag-blocking slide brick and its preparation method proposed by the present invention use ZrB2 and Al3BC3 as core reinforcement materials, optimize the material cost, and replace the high-content zirconium oxide in the expensive inlaid zirconium slide. While maintaining high performance, it significantly reduces the production cost and has the economic feasibility of large-scale promotion.

[0053] 6. The present invention proposes a composite reinforced high-temperature durable converter slag-blocking slide brick and a preparation method thereof. During the pouring of molten steel, the slide material will experience drastic temperature changes, which can easily lead to the formation of thermal shock cracks. Al3BC3 and other components have certain high-temperature creep resistance, can effectively absorb part of the heat, disperse thermal stress, and slow down the expansion of cracks. Maintaining a high structural stability of the matrix helps to reduce thermal stress when the temperature fluctuates rapidly. DETAILED DESCRIPTION

[0054] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Example 1

[0056] This embodiment provides the following technical solutions:

[0057] A composite enhanced high-temperature durable converter slag-blocking slide brick comprises granular material, premixed powder and a binder, wherein the components and mass fractions of the granular material are as follows:

[0058]

[0059] The components and mass fractions of the premixed powder are as follows:

[0060]

[0061]

[0062] The components and mass fractions of the binder are:

[0063] 2-4 parts of thermosetting phenolic resin;

[0064] 2 to 4 parts of silicone resin.

[0065] In this embodiment, w(Al2O3) in fused zirconium corundum is ≥72.5%, w(SiC) in silicon carbide is >98wt%; w(Al2O3) in granular plate-like corundum and plate-like corundum powder is ≥99%, and the volume density of granular plate-like corundum is 3.5g·cm-3; w(C solid content) in thermosetting phenolic resin is ≥50%.

[0066] Al3BC3 micropowder has a series of excellent properties. It has low density, high hardness, high melting point, high thermal stability and good antioxidant properties. It maintains high yield strength at high temperatures. It is a good antioxidant in carbon-containing refractory materials and has excellent anti-hydrolysis properties. It can also withstand drastic temperature changes. For example, the performance of the material is maintained well when it is rapidly cooled from 1500°C to room temperature.

[0067] ZrB2 micro powder zirconium diboride (ZrB2) is a typical ultra-high temperature ceramic material belonging to the hexagonal crystal system. It has the characteristics of high melting point (3245℃), high hardness, corrosion resistance and good chemical stability.

[0068] In this embodiment, in the metal aluminum powder, w(Al)≥99.5%; the mesh size is 500 mesh, and the metal aluminum is formed by high pressure forming to form a metal plastic bond, thereby improving the strength of the brick; and the metal aluminum forms non-oxides at high temperatures to produce whiskers that change the microstructure of the material to densify and close the pores. 4A1+302→2Al2O3, aluminum can also react with components such as boron carbide (BC) and carbon black (C) at high temperatures to generate hard phases such as AIC, AIB and Al3BC3. These hard phases can not only improve the wear resistance of the material under high temperature conditions, but also improve the erosion resistance, i.e. 9Al+2B4C→2Al3BC+3AlB2.

[0069] In this embodiment, the particle size of a-Al2O3 micropowder is 0-3μm; the chemical composition and main content of a-Al2O3 micropowder are: Al2O3 content ≥99.0wt%, SiO2 content ≤0.1wt%, Fe2O3 content ≤0.08wt%, Na2O+K2O content ≤0.3wt%.

[0070] In this embodiment, in the silicon carbide powder, w(SiC)≥99%, the particle size is 3μm, and the silicon carbide powder has the characteristics of high hardness, high wear resistance, good self-lubrication, high thermal conductivity, low thermal expansion coefficient and high high temperature strength. Silicon carbide (SiC) has extremely high hardness (Mohs hardness of about 9.5), second only to diamond. Therefore, SiC, as a hard phase in the skateboard material, can play the role of a wear-resistant skeleton during the molten steel pouring process, reducing the direct contact between the molten steel and the skateboard material, thereby reducing the loss and wear rate of the skateboard.

[0071] In this embodiment, the boron carbide powder has a Mohs hardness of 9.3, a relative density (d204) of 2.508-2.512, and a melting point of 2350°C.

[0072] In order to better demonstrate the process of realizing a composite enhanced high-temperature durable converter slag-blocking slide brick, this embodiment proposes a method for preparing a composite enhanced high-temperature durable converter slag-blocking slide brick, comprising the following steps:

[0073] S1. First, mix the granular materials evenly according to the proportion;

[0074] S2, then dry-mixing the composite powders in proportion under vacuum conditions to form a premixed powder;

[0075] S3, then the granular material, premixed powder, thermosetting phenolic resin and silicone resin are mixed at high speed;

[0076] S4. Finally, the finished product is obtained after pressing, drying and fine processing.

[0077] The raw material components and proportions of the above-mentioned granular material, premixed powder and binder are used to prepare a composite enhanced high-temperature durable converter slag-blocking slide brick of this embodiment. The mass ratio of Al3BC3 micropowder, metal aluminum powder, ZrB2 micropowder and graphite is 4:3:4. The specific preparation steps are as follows:

[0078] S1. Ingredients of granular materials: granular materials are prepared according to the mass proportion of raw materials; 15 parts of 3-1 mm fused zirconium corundum, 25 parts of 2-1 mm plate corundum, 15 parts of 1-0 mm plate corundum, and 5 parts of 1-0 mm silicon carbide;

[0079] S2, premixed powder: 18 parts of 325 mesh plate-shaped corundum fine powder, 3 parts of 325 mesh Al3BC3 micro powder, 3 parts of 3 μm mesh ZrB2 micro powder, 2 parts of 1000 mesh SiC powder, 4 parts of 500 mesh metal Al powder, 1 part of 325 mesh boron carbide and 1 part of carbon black were dry-mixed in a vacuum high-speed mixer for 30 minutes to evenly disperse the fine powder components. After dispersion, the mixture was bagged and sealed for later use;

[0080] S3, high-speed mixing: mix the granular material prepared in step 1 with the premixed powder in step 2, and add 1 part of thermosetting phenolic resin and 3 parts of high-temperature silicone resin and mix for 10-15 minutes. After mixing evenly, place the slurry in a constant temperature room for 8-10 hours. The constant temperature room is required to maintain a temperature of 25±3°C and a relative humidity of 45-65%.

[0081] S4, molding: The clay trapped in the constant temperature and humidity chamber in step 3 is molded into semi-finished blanks using a LAEIS 2500-ton hydraulic press, and the density of the blank is controlled to be no less than 3.10g / cm 3 ;

[0082] S5. Drying: After the green body is naturally aired for 12 hours, it is placed in a gas drying kiln for drying, and the temperature is raised from room temperature to 80°C within 4 hours, and kept warm for 2 hours → the temperature is raised from 80°C to 120°C within 4 hours, and kept warm for 2 hours → the temperature is raised from 120°C to 150°C within 3 hours, and kept warm for 2 hours → the temperature is raised from 150°C to 180°C within 3 hours, and kept warm for 2 hours → the temperature is raised from 180°C to 210°C within 3 hours, and kept warm for 10 hours;

[0083] S6. High temperature firing: stack the dried bricks vertically and put them into silicon carbide saggers, bury the carbon particles and seal them well, then put them into high temperature shuttle kiln for firing. The highest firing temperature is 1500℃. The specific firing process curve is as follows: room temperature ~ 300℃, 10 hours → 300 ~ 900℃, 25 hours → 900 ~ 1350℃, 15 hours → 1350 ~ 1500℃, 10 hours → 1500℃, keep warm for 10 hours and stop firing, dry the kiln → the kiln temperature drops to 200℃, open the kiln door and cool naturally;

[0084] S7, making steel hoops: after the fired product in step 5 is cooled to room temperature, a Q235 cold-rolled steel hoop with a thickness of 5 mm and a width of 35 mm is hot-fitted on the converter slide body to prevent the expansion and extension of cracks caused by temperature changes when the product is used in the steel plant;

[0085] S8, grinding: the converter slide brick with steel hoop in step 6 is finely ground by CNC grinder, and after the flatness reaches 0.03mm, it is infrared dried at 200℃ for 0.5h and then prepared for the next process;

[0086] S9, coating: coating the skateboard bricks finely ground in step 7 with a special high temperature resistant coating, and obtaining the finished product after natural drying.

[0087] Example 2

[0088] This embodiment provides a composite reinforced high-temperature durable converter slag retaining slide brick, the raw material composition of which is in accordance with the formula shown in Table 1, and the preparation method is the same as that of Example 1.

[0089] Example 3

[0090] This embodiment provides a composite reinforced high-temperature durable converter slag retaining slide brick, the raw material composition of which is in accordance with the formula shown in Table 1, and the preparation method is the same as that of Example 1.

[0091] Example 4

[0092] This embodiment provides a composite reinforced high-temperature durable converter slag retaining slide brick, the raw material composition of which is in accordance with the formula shown in Table 1, and the preparation method is the same as that of Example 1.

[0093] Examples 1 to 4 The raw material formula of a composite enhanced high temperature durable converter slag blocking slide brick is shown in Table 1:

[0094] Table 1 Formula of each raw material mass fraction in Examples 1 to 4

[0095]

[0096] Next, the performance test was carried out using the composite reinforced high temperature durable converter slag retaining slide bricks prepared in Examples 1 to 4. The results are shown in Table 2.

[0097] A composite reinforced high-temperature durable converter slag-blocking slide brick performance test, according to GB / T2997-2000, GB / T3001-2007GB / T5072-2008, the volume density, apparent porosity, room temperature flexural strength and compressive strength of the strip sample after 200℃ baking are measured; according to GB / T13243-1991, the high temperature flexural strength of the strip sample after 200℃ baking (1500℃ insulation for 1h, buried in carbon) is measured; according to YB / T4018-1991, the thermal shock resistance is tested, the strip sample after 200℃ baking is buried in carbon and heated to 1100℃ for 1h, then taken out and air-cooled, after repeating 3 times, the residual flexural strength (room temperature) is tested, and the flexural strength retention rate is used to characterize the thermal shock resistance. The cylindrical sample after 200℃ baking is oxidized in the high temperature oxidation furnace at 1500℃ for 3h in air, and the thickness of the oxide layer of the cross section of the sample after oxidation is measured.

[0098] Table 2 Performance of composite reinforced high temperature durable converter slag retaining slide brick

[0099]

[0100] Through a series of high temperature performance tests, the performance data of composite skateboard materials under different conditions were obtained, mainly including:

[0101] Bulk density and apparent porosity: At 200°C and 1300°C, the skateboard material exhibits excellent density and low porosity (apparent porosity is 3.4% to 5.6%), which indicates that the material has good structural stability.

[0102] Flexural strength and compressive strength: The flexural strength can reach 65-72MPa at room temperature, and it can still maintain a flexural strength of about 42-49MPa at 1300℃, showing good high-temperature mechanical properties. In addition, the compressive strength at room temperature and high temperature reached 192-211MPa and 143-149MPa respectively, ensuring the strength and durability of the material.

[0103] High temperature flexural strength: At a high temperature of 1500℃, the flexural strength of the skateboard material remains at 52-55MPa, showing good high temperature strength.

[0104] Flexural strength retention rate: After 1100℃ thermal shock treatment, the flexural strength retention rate is 78% to 82%, indicating that the material has excellent thermal shock stability and can effectively resist crack propagation caused by temperature fluctuations.

[0105] Oxide layer thickness: Under the oxidation condition of 1500℃, the oxide layer thickness of the material is 1.7-1.9mm, which is much lower than the oxidation loss of traditional materials, indicating that this material has strong oxidation resistance and effectively delays the consumption of the oxide layer.

[0106] The scheme of the present invention is used in the following specific usage: the finished product is used in the converter steelmaking process of a northern steel plant in China. Since the converter steelmaking environment is rich in oxidizing atmosphere, the oxidation loss of the slide plate directly affects its service life. Traditional slide plates need to be replaced more frequently every month, between 12 and 18 furnaces, which affects the efficiency and cost of converter steelmaking. This material generates a dense composite oxidation protective layer at 1500°C, which blocks the further penetration of oxygen and oxides and delays the oxidation wear of the slide plate. This plays a positive role in reducing the surface loss of the slide plate and improving the slag blocking efficiency. The actual service life can be extended to 1.5 times, and the average number of furnaces reaches 24 furnaces, which greatly reduces the replacement cost of the slide plate and the cost of shutdown and maintenance. It meets the requirements of modern smelting processes for high-performance refractory materials and is an innovative solution with broad promotion prospects.

[0107] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A composite reinforced high temperature durable converter slag retaining slide brick, characterized in that: It includes granular material, premixed powder and binder, and the components and mass fractions of the granular material are as follows: The components and mass fractions of the premixed powder are as follows: The components and mass fractions of the binder are as follows: 2-4 parts of thermosetting phenolic resin; 2 to 4 parts of silicone resin.

2. The composite reinforced high temperature durable converter slag retaining slide brick according to claim 1, characterized in that: The w(Al2O3) in the fused zirconium corundum is ≥72.5%, the w(SiC) in the silicon carbide is >98wt%; the w(Al2O3) in the granular plate-like corundum and the plate-like corundum powder is ≥99%, and the volume density of the granular plate-like corundum is 3.5g·cm-3; the w(C solid content) in the thermosetting phenolic resin is ≥50%.

3. The composite reinforced high temperature durable converter slag retaining slide brick according to claim 2, characterized in that: In the metal aluminum powder, w(Al)≥99.5%; the mesh size is 500 meshes.

4. The composite reinforced high temperature durable converter slag retaining slide brick according to claim 3, characterized in that: The particle size of the a-Al2O3 micropowder is 0-3 μm; the chemical composition and main content of the a-Al2O3 micropowder are: Al2O3 content ≥99.0wt%, SiO2 content ≤0.1wt%, Fe2O3 content ≤0.08wt%, Na2O+K2O content ≤0.3wt%.

5. The composite reinforced high temperature durable converter slag retaining slide brick according to claim 4, characterized in that: In the silicon carbide powder, w(SiC)≥99% and the particle size is 3 μm.

6. The composite reinforced high temperature durable converter slag retaining slide brick according to claim 5, characterized in that: The boron carbide powder has a Mohs hardness of 9.3, a relative density (d204) of 2.508-2.512, and a melting point of 2350°C.

7. The method for preparing a composite reinforced high-temperature durable converter slag retaining slide brick according to claim 6, characterized in that: The steps include: S1. First, mix the granular materials evenly according to the proportion; S2, then dry-mixing the composite powders in proportion under vacuum conditions to form a premixed powder; S3, then the granular material, premixed powder, thermosetting phenolic resin and silicone resin are mixed at high speed; S4. Finally, the finished product is obtained after pressing, drying and fine processing.

8. The method for preparing a composite reinforced high-temperature durable converter slag retaining slide brick according to claim 7, characterized in that: The steps of preparing a composite enhanced high-temperature durable converter slag-blocking slide brick by using the raw material components and proportions of the granular material, premixed powder and binder are as follows: S1. Ingredients of granular materials: granular materials are prepared according to the mass proportion of raw materials; 15 parts of 3-1 mm fused zirconium corundum, 25 parts of 2-1 mm plate corundum, 15 parts of 1-0 mm plate corundum, and 5 parts of 1-0 mm silicon carbide; S2, premixed powder: 20 parts of 325 mesh plate-shaped corundum fine powder, 3 parts of 325 mesh Al3BC3 micropowder, 3 parts of 3μm mesh ZrB2 micropowder, 8 parts of a-Al2O3 micropowder, 2 parts of 1000 mesh SiC powder, 5 parts of 500 mesh metal Al powder, 1 part of 325 mesh boron carbide, and 1 part of carbon black were dry-mixed in a vacuum high-speed mixer for 30 minutes to evenly disperse the fine powder components. After dispersion, the fine powder components were packed and sealed for later use; S3, high-speed mixing: the granular material prepared in step 1 is mixed with the premixed powder in step 2, and thermosetting phenolic resin and high-temperature silicone resin are added and mixed for 10 to 15 minutes. The mixed mud is kept in a constant temperature room for 8 to 10 hours. The constant temperature room is required to maintain a temperature of 25 ± 3 ° C and a relative humidity of 45 to 65%; S4, molding: the clay trapped in the constant temperature and humidity chamber in step 3 is molded into semi-finished blanks using a LAEIS 2500-ton hydraulic press; S5, drying: the semi-finished blank prepared in step 4 is naturally cooled for 12 to 16 hours, and then enters the electric kiln dryer. The drying temperature is divided into two stages. The first stage is heated at a uniform rate of 20°C per hour to 110°C and then kept warm for 24 hours. The second stage is heated at a uniform rate of 15°C per hour to 300°C and kept warm for 24 hours. S6, making steel hoops: after the fired product in step 5 is cooled to room temperature, a Q235 cold-rolled steel hoop with a thickness of 5 mm and a width of 35 mm is hot-fitted on the converter slide body to prevent the expansion and extension of cracks when the product is used; S7, grinding: the converter slide brick with steel hoop in step 6 is finely ground by CNC grinder, and after the flatness reaches 0.03mm, it is infrared dried at 200℃ for 0.5h and then prepared for the next process; S8, coating: coating the skateboard bricks finely ground in step 7 with a special high temperature resistant coating, and obtaining the finished product after natural drying.

9. The method for preparing a composite reinforced high-temperature durable converter slag retaining slide brick according to claim 8, characterized in that: In the step 2, a planetary vibrating high-energy ball mill is used for vacuuming; in the step 3, an EIRICH high-power mixer is used for uniform mixing.